Paris lihengiana (Melanthiaceae: Parideae), a new species from Yunnan, China - Xu, Zhun; Wei, Neng; Tan, Ying; Peng, Shuai; Ngumbau, Veronicah Mutele; Hu, Guang-Wan; Wang, Qing-Feng (Phytotaxa, 2019)
Paris lihengiana (Melanthiaceae), a new species from Yunnan Province, China, is described and illustrated based on evidence from morphological characters and molecular phylogeny. It differs from other species of Paris in its pubescent stem, pedicel and abaxial leaf surface, as well as other characters. Molecular phylogenetic analysis of 33 taxa in Paris was conducted based on nuclear ribosomal ITS and six plastid markers. Paris lihengiana is supported as a new species by both morphological characters and molecular data.